Topical Dimethyl Sulfoxide for Congested Nipple–areolar Complexes in Breast Surgery: A Pilot Study. Issue 10 (28th October 2022) - Silverstein, Max L.; McLean, Paige; Crowley, Jiwon S.; Gosman, Amanda A.
Abstract : Background: Necrosis of the nipple–areolar complex (NAC) is a major complication of breast surgery that most commonly results from venous congestion. Several conservative rescue therapies have been proposed for relieving NAC congestion, but each carries certain drawbacks, including cost and side effect profile. In this study, we evaluated the effectiveness of topical dimethyl sulfoxide (DMSO), an inexpensive compound with vasodilatory, free radical scavenging, and antiinflammatory properties in rescuing congested NACs. Methods: We conducted a review of all 15 patients treated with DMSO for NAC congestion at our institution between May 2019 and October 2020. DMSO was applied in liquid form on a soaked gauze pad in the hospital; patients were instructed to apply a DMSO cream to the NAC twice a day following discharge. Patient characteristics and data related to DMSO treatment and NAC healing were compared via univariate analysis. Results: Eighteen congested NACs from 15 patients who underwent mastectomy, breast reduction, mastopexy, or breast reconstruction were treated with DMSO. Of the 18 treated NACs, 15 healed with DMSO treatment alone. The average length of DMSO treatment was 9.4 ± 8.5 days (mean ± standard deviation); NAC healing took place over 9.9 ± 9.6 days. There were no complications related to DMSO treatment. Conclusions: This pilot study shows that DMSO may be an effective topical treatment for NAC congestion following breast surgery. Given its low cost, ease of application, and lack of side effects, future studies should prospectively compare DMSO against other topical treatments, like nitroglycerin ointment.